(untitled) (Fiep Bulletin - online, 2011)
The World-wide Organization of Health (OMS) praises the use of the circumference of the waist in the point of cut of 92 cm for men and 88 cm for women, as measured of increased metabolic risk, despite diverse methods can be used in the characterization of the distribution of the fabric fat. The knowledge of these points of cut is useful in the detention of the risk of development of illnesses, as much in the nutritional monitoring how much in studies of population diagnosis. The study it searched to verify the index of risk of the population of Cabo Frio/RJ Handle in relation the coronarianas illnesses and if it would be practices possible it of physical activities through the protocol of ICQ and the questionnaire of PAR-Q. 38 adult being 12 of masculine sex and 26 of the feminine sex, previously sedentary, living individuals of the city of handle had participated of this study Cabo Frio/RJ region of the lakes. In the relation masculine age and ICQ (ID = 48/ICQ: 0.95), the moderate risk and in the feminine sex (ID = 44/ICQ: 0.83), the high risk and. The great concentration of high risk of the ICQ was verified that in the feminine sex this in the etária band of 34 the 49 years where it was observed pains in the chest and problems osteoarticulares. No longer was masculine group verified that it has a moderate risk with a heterogeneous distribution between the ages. One evidenced a moderate risk in the etária band of 24 the 31 years and 71 and 72 years, where it was observed pains in the chest and problems osteoarticulares.